Consumption and Production Survey of Thin Chicken Sausages in Benin - Gbaguidi, Mauricette; kpatinvoh, Brice; DEGNON, GNIMABOU RENÉ; CHOUGOUROU, CHÈPO DANIEL (My University, 2021)
The work aims to carry out a survey on the production and consumption of sausage in Benin. Indded, the sausage constitutes a source of protein and the surveys were carried out in the various communes of Benin, on the basis of a reasonable sample of 120 consumers and food sellers in each department of Benin. These surveys relate to the production of chicken sausage which is done according to the different stages which are the pre-treatment of raw materials, bonig, trimming, chopping, cutting, embossing, draining, druing and sterilization. These result showed that the majority of consumers surveyed use Minu and Morifresh brand sausages to accompany meals rich in protein. The results also showed that the different types of sausages are used to accompany several culinary dishes in Benin.
Keywords: Sausage; Production; Consomption; Benin.